Overview of Mothers Knowledge and Attitudes about Baby Spa in Independent Practice Midwife Hj. Kokom Komariah at Cipondoh Tangerang - Hidayat, Nurani (STIKes RSPAD RSPAD Gatot Soebroto, 2024)
Spa (solus per aqua) is a treatment or treatmentusingwater as a medium. Baby Spa is a body spa treatment for babiesthatcan bedone in 2 ways, namely, bathing, or swimming and massage. The aim of this study is to describe the knowledge and attitudes of mothers about baby spa in Independent Pactice Midwife Hj. Kokom Komariah Cipondoh Tangerang. The author made observations in independent practice midwife hj. Kokom komariah cipondoh tangerang by conducting oral interviews with 10 mothers who have babies by asking questions about the meaning and benefits of a baby spa, and the results were 7 ofwich were unable to answer the meaning andbenefits of a baby spa. Result shows that the of knowledge about baby spa 15 respondents have less knowledge (50%), 10 respondents (33%) have sufficient knowledge, 5 respondents (17%) have good knowledge and10 respondents (33,3%)have a positive attitude, while 20 respondents have negative attitudes (66,7%). The conclusion shows that the knowledge about baby spa 15respondents have less knowledge (50%) and negative attitudes (66,7%). It is suggested to increase and add research knowledge about the knowledge and attitudes of mothers about baby spa